SALAFI THOUGHT AS THE BASIS OF COUNTER-RADICALISM: AN EMPIRICAL STUDY OF KPI ALUMNI OF STAI AS-SUNNAH KPI IN THE PERSPECTIVE OF ISLAMIC LAW: PEMIKIRAN SALAFI SEBAGAI BASIS KONTRA-RADIKALISME: STUDI EMPIRIS TERHADAP ALUMNI KPI STAI AS-SUNNAH DALAM PERSPEKTIF HUKUM ISLAM - Hamdani Hamdani; Zulkarnain Zulkarnain; Dhiauddin Tanjung (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the contribution of Salafi understanding among alumni of the Islamic Communication and Broadcasting (KPI) Program at STAI As-Sunnah Tanjung Morawa in countering terrorism-related ideologies in Indonesia. Amid the widespread dissemination of radical ideologies, especially among youth through social media and educational institutions, authentic Salafi teachings offer a moderate and non-violent religious approach. Although STAI As-Sunnah does not formally identify itself as a Salafi institution, the educational and preaching orientation of its alumni reflects a strong adherence to the values of the Salafus Shalih. This research adopts a quantitative approach using a correlational method. A sample of 35 alumni was selected through purposive sampling, and data were collected via a closed-ended questionnaire that had been tested for validity and reliability. The findings indicate that alumni possess a very high level of Salafi understanding, accompanied by a strong attitude against terrorism. There is a very strong correlation between Salafi understanding and anti-terrorism attitudes, with the former significantly contributing to ideological resilience against radicalism. The study concludes that proper and balanced Salafi understanding plays a vital role in shaping moderate religious attitudes and supports deradicalization efforts within the Indonesian Muslim community, particularly among the younger generation.